1988
DOI: 10.1177/036354658801600502
|View full text |Cite
|
Sign up to set email alerts
|

Long-term evaluation of knee stability and function following surgical reconstruction for anterior cruciate ligament insufficiency

Abstract: Currently used measures of knee stability and function for ACL reconstructed knees have not gained universal acceptance. Clinical test results often are given more value than the patient's subjective evaluation of the surgical outcome. This study was designed to identify specific knee stability and function variables that were most predictive of the patient's rating of knee function following one of two types of combined (intraarticular and extraarticular) ACL reconstruction procedures. Individual measures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
1
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(89 citation statements)
references
References 26 publications
(11 reference statements)
6
80
1
2
Order By: Relevance
“…This lack of methodological scientific evidence may explain why many studies have shown no difference in anterior laxity after different types of surgical reconstruction between a bone-patellar tendon-bone (BPTB) and a semitendinosus (ST) autograft [92][93][94]. However, two meta-analyses comparing the two main graft types (BPTB vs. ST) have demonstrated that a SSD superior to 3 mm was less frequent in BTPB compared to ST grafts [95,96].…”
Section: Knee Laxity After Anterior Cruciate Ligament Reconstructionmentioning
confidence: 99%
“…This lack of methodological scientific evidence may explain why many studies have shown no difference in anterior laxity after different types of surgical reconstruction between a bone-patellar tendon-bone (BPTB) and a semitendinosus (ST) autograft [92][93][94]. However, two meta-analyses comparing the two main graft types (BPTB vs. ST) have demonstrated that a SSD superior to 3 mm was less frequent in BTPB compared to ST grafts [95,96].…”
Section: Knee Laxity After Anterior Cruciate Ligament Reconstructionmentioning
confidence: 99%
“…In four of the patients when physiotherapy was not followed or was inadequately performed the results were inferior. Physiotherapy does indeed contribute significantly to good results (8,9,18,19). …”
Section: Discussionmentioning
confidence: 98%
“…These include direct repair, extra-articular procedures (6,7) and intra-articular prostheses (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Even though the use of the bone-patellar tendon-bone autograft is considered the gold standard for ACL reconstruction by some surgeons, the quadriceps has many disadvantages such as weakness in muscle strength, loss of full extension and anterior knee pain in the postoperative period. 12,13 In a reconstruction with hamstring tendons, the preservation of the extensor mechanism prevents atrophy of the quadriceps muscle, and problems such as postoperative knee pain and extension deficit are rarely encountered. 14,15 The donor-site morbidity of hamstring tendons is much lower compared to that of the patellar tendon.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 The donor-site morbidity of hamstring tendons is much lower compared to that of the patellar tendon. 12,13 Since the crosssection area is larger compared to that in the patellar tendon, vascularization is also easier. 16,17 Hamstring tendons are biomechanically superior to the patellar tendon.…”
Section: Discussionmentioning
confidence: 99%